Encountering Terra Australis : the Australian Voyages of Nicolas Baudin and Matthew Flinders. - Fornasiero, F. J. (Wakefield Press, 2011)
Encountering Terra Australis traces the parallel lives and voyages of the explorers Flinders and Baudin, as they travelled to Australia and explored the coastline of mainland Australia and Tasmania.